2006
DOI: 10.1038/ng1936
|View full text |Cite
|
Sign up to set email alerts
|

A viable allele of Mcm4 causes chromosome instability and mammary adenocarcinomas in mice

Abstract: Mcm4 (minichromosome maintenance-deficient 4 homolog) encodes a subunit of the MCM2-7 complex (also known as MCM2-MCM7), the replication licensing factor and presumptive replicative helicase. Here, we report that the mouse chromosome instability mutation Chaos3 (chromosome aberrations occurring spontaneously 3), isolated in a forward genetic screen, is a viable allele of Mcm4. Mcm4(Chaos3) encodes a change in an evolutionarily invariant amino acid (F345I), producing an apparently destabilized MCM4. Saccharomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
351
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(379 citation statements)
references
References 29 publications
24
351
3
1
Order By: Relevance
“…In two of our tumors with MCM4 mutations, this association could be defined mechanistically by genomic alteration of the family of MCM2-7 genes (43). Consistent with this hypothesis, prior studies have shown that Mcm protein deficiencies result in high rates of cancer in mouse models (44,45), catastrophic chromosomal rearrangements in human lymphoblasts in culture (46), and complex chromosomal alterations at discrete locations that are consistent with chromothripsis (43).…”
Section: Discussionsupporting
confidence: 60%
“…In two of our tumors with MCM4 mutations, this association could be defined mechanistically by genomic alteration of the family of MCM2-7 genes (43). Consistent with this hypothesis, prior studies have shown that Mcm protein deficiencies result in high rates of cancer in mouse models (44,45), catastrophic chromosomal rearrangements in human lymphoblasts in culture (46), and complex chromosomal alterations at discrete locations that are consistent with chromothripsis (43).…”
Section: Discussionsupporting
confidence: 60%
“…However, deregulation of the licensing system may also be a primary driver of oncogenesis, at least in some tumour types. For example, over-expression of Cdc6 or Cdt1 have been shown to be oncogenic, and deregulated Mcm7 expression has been linked to tumour formation, progression and malignant transformation in animal models [84][85][86][87][88][89][90]. Oncogenic mutations in genes upstream of the licensing machinery (eg RAS, CYCLINE and CYCLIND1 ) can also impact on tumourigenesis by causing deregulation of the licensing machinery.…”
Section: Dna Replication Licensing and Cancermentioning
confidence: 99%
“…More recently, two mouse models that recapitulate MCM loss-of-function situations have been reported. In the first one, a hypomorphic mutation in Mcm4 caused chromosome instability and increased the susceptibility to mammary adenocarcinomas (30). In the second one, a genetic manipulation of the 3Ј UTR in the MCM2 gene resulted in a mouse strain that expresses only a third of the normal concentration of Mcm2 protein.…”
Section: Dosage In Metazoanmentioning
confidence: 99%